2022
DOI: 10.3390/jcm11154521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Myocarditis following COVID-19 mRNA Vaccination: A Systematic Review and Meta-Analysis

Abstract: COVID-19 mRNA vaccinations have recently been implicated in causing myocarditis. Therefore, the primary aim of this systematic review and meta-analysis was to investigate the clinical characteristics of patients with myocarditis following mRNA vaccination. The secondary aims were to report common imaging and laboratory findings, as well as treatment regimes, in these patients. A literature search was performed from December 2019 to June 2022. Eligible studies reported patients older than 18 years vaccinated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 125 publications
0
7
0
Order By: Relevance
“…The global rate of COVID-19 vaccination is increasing rapidly. [3][4][5] Although vaccinations significantly protect us from viral infections, there is increasing evidence of various cardiovascular adverse events after vaccination for COVID-19, including cardiac arrythmias. Our systematic review and meta-analysis showed that the incidence of arrhythmia was significantly higher in people who received COVID-19 vaccines than in people who received non-COVID-19 vaccines (Figure 2), with the exception of smallpox vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The global rate of COVID-19 vaccination is increasing rapidly. [3][4][5] Although vaccinations significantly protect us from viral infections, there is increasing evidence of various cardiovascular adverse events after vaccination for COVID-19, including cardiac arrythmias. Our systematic review and meta-analysis showed that the incidence of arrhythmia was significantly higher in people who received COVID-19 vaccines than in people who received non-COVID-19 vaccines (Figure 2), with the exception of smallpox vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although COVID-19 vaccines are generally considered safe, adverse events after vaccination, such as thromboembolisms, myocarditis, and arrhythmia, are increasingly being reported. [3][4][5] Arrhythmias are a known but rare adverse reaction to viral vaccination and have also occurred after other vaccinations, including those for smallpox and human papillomavirus (HPV). [6][7][8] The mRNA COVID-19 vaccines trigger innate immunity, cytotoxicity, and helper T cells, especially B cells, to promote the induction of neutralizing antibodies 9 ; however, these reactions can also affect the cardiovascular system and cause serious adverse events, including arrhythmia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to cardiovascular medicine, it is desirable to know specific genetic risk factors for the development of myocarditis during COVID-19 or upon vaccination [112,[165][166][167][168][169][170][226][227][228][229][230][231][232], or for development of long COVID syndromes [191,[233][234][235][236][237][238][239]. Fortunately, SARS-CoV-2 is rather rarely causing severe myocarditis or cardiomyopathies [165][166][167][168][169][170].…”
Section: Cardiovascular Immunobiology Of Covid-19 and Long Covid Synd...mentioning
confidence: 99%
“…With regard to cardiovascular medicine, it is desirable to know specific genetic risk factors for the development of myocarditis during COVID-19 or upon vaccination [112,[164][165][166][167][168][169][204][205][206][207][208][209], or for development of long COVID syndromes [190,[210][211][212][213].…”
Section: Cardiovascular Immunobiology Of Covid-19 and Long Covid Synd...mentioning
confidence: 99%